IDENTIFICATION OF BASE SECTORS IN PACITAN REGENCY BASED ON LOCATION QUOTIENT (LQ) ANALYSIS FOR THE 2014–2023 PERIOD (Proceeding of SINERGY, 2026)
This study aims to identify the economic base sectors of Pacitan Regency during the 2014–2023 period using the Location Quotient (LQ) method. The data utilized are Gross Regional Domestic Product (GRDP) data of Pacitan Regency and East Java Province at constant prices. The analysis results indicate that eight sectors serve as the economic base of the region, namely agriculture, forestry, and fisheries; mining and quarrying; construction; information and communication; public administration; education; health; and other services. The agriculture sector recorded the highest LQ value of 2.358, indicating the dominance of natural resource–based economic activities. However, the construction and information–communication sectors showed increasing LQ values, reflecting a gradual shift toward more productive sectors. These findings are expected to serve as a reference for formulating regional development policies focused on economic diversification and strengthening potential sectors to support sustainable regional growth.